Long-term effect on symptoms and quality of life of maintenance therapy with esomeprazole 20 mg daily: a post hoc analysis of the LOTUS trial. (31st October 2014) - Lundell, Lars; Hatlebakk, Jan; Galmiche, Jean-Paul; Attwood, Stephen E.; Ell, Christian; Fiocca, Roberto; Persson, Tore; Nagy, Péter; Eklund, Stefan; Lind, Tore
Abstract: Objective: To assess the long-term effect on symptoms and quality of life of esomeprazole 20 mg once daily, a recommended dose for maintenance therapy of gastroesophageal reflux disease (GERD). Research design and methods: This is a post hoc analysis of 5 year data from patients in the LOTUS trial (ClinicalTrials.gov identifier: NCT00251927) who were randomized to esomeprazole 20 mg once daily. All participants had chronic, symptomatic GERD responsive to treatment. Gastrointestinal symptoms were assessed by physicians and by using patient-reported outcome instruments. Investigations included gastrointestinal endoscopy (with biopsy sampling), 24 hour esophageal pH monitoring and laboratory measurements. Results: In total, 157 of 256 patients randomized to esomeprazole 20 mg once daily remained on this dose until the end of follow-up or study discontinuation, whereas 99 patients had their dose increased because of inadequate symptom control (of these, 29 subsequently returned to the allocated dose). On logistic regression, a long objectively defined GERD history, smoking, female sex, absence of Helicobacter pylori infection and high supine baseline acid reflux into the esophagus were associated with an increased likelihood of requiring dose escalation to esomeprazole 40 mg daily (all p < 0.05). Symptoms were fairly stable and quality of life was normal throughout follow-up in patients remaining on esomeprazole 20 mg once daily, with no more than mild symptom severity, and mean (standard deviation) percentage time with intraesophageal pH <4 was reduced from 10.7 (10.7) pre-randomization to 6.3 (10.2) at 6 months and 4.9 (7.3) at 5 years. The number of serious adverse events was low (0.079 per patient per year). Limitations: Post hoc analysis with no control group. Conclusions: Esomeprazole at a maintenance dose of 20 mg once daily offers effective long-term treatment for chronic GERD in patients initially responsive to the medication, with durable symptom control and sustained reductions in intraesophageal acid exposure.